Protocol of a prospective, monocentric phase I/II feasibility study investigating the safety of multimodality treatment with a combination of intraoperative chemotherapy and surgical resection in locally confined or borderline resectable pancreatic cancer: the combiCaRe study - Roth, Susanne; Springfeld, Christoph; Diener, Markus K.; Tjaden, Christin; Knebel, Phillip; Klaiber, Ulla; Michalski, Christoph; Mieth, Markus; Jäger, Dirk; Büchler, Markus W.; Hackert, Thilo (BMJ open, 2019)
Introduction: Pancreatic cancer is a devastating disease with an exceptionally poor prognosis. Complete resection of the primary tumour followed by adjuvant chemotherapy is the current standard treatment for patients with resectable disease and the only curative treatment option. However, long-term survival remains rare. Tumour cell dissemination due to manipulation during surgery may increase the rate of future metastases and local recurrence, and perioperative chemotherapy might diminish local, distant and circulating minimal residual disease. Yet, safety and feasibility of systemic chemotherapeutic treatments during pancreatic cancer resection have to be evaluated in a first instance. - Methods and analysis: This is a prospective, single-centre phase I/II feasibility study to investigate the safety and tolerability of a combination of intraoperative chemotherapy and surgical resection in pancreatic cancer. Forty patients with locally confined or borderline resectable pancreatic cancer, meeting all proposed criteria will be included. Participants will receive 400 mg/m2 calcium folinate over 2 hours and 2000 mg/m2 5-fluorouracil over 48 hours, started on the day before pancreatic surgery and thus continuing during surgery. Participants will be followed until 60 days after surgery. The primary endpoint is the 30-day overall complication rate according to the Clavien-Dindo classification. Secondary endpoints comprise toxicity and treatment associated complications. Patients receiving perioperative chemotherapy will be compared with a propensity score matched contemporary control group of 70 patients with pancreatic cancer receiving the standard treatment. This trial also contains an ancillary translational study to analyse disseminated tumour cells and effects of pharmacological interventions in pancreatic cancer. - Ethics and dissemination: CombiCaRe has been approved by the German Federal Institute for Drugs and Medical Devices (reference number 4042787) and the Medical Ethics Committee of Heidelberg University (reference number AFmo-269/2018). The results of this trial will be presented at national and international conferences and published in peer-reviewed journals. - Trial registration number: German Clinical Trials Register (DRKS00015766).